ChemInform Abstract: Asymmetric Synthesis of 1H‐Pyrrol‐3(2H)‐ones from 2, 3‐Diketoesters by Combination of Aldol Condensation with Benzilic Acid Rearrangement. Issue 18 (April 2016) - Sha, Qiang; Arman, Hadi; Doyle, Michael P.
Abstract: A new two‐step method for the highly enantioselective synthesis of 1H‐pyrrol‐3(2H)‐ones is reported using 2, 3‐diketoesters in asymmetric aldol reactions for the first time.